Mitigating Soil Phosphorus Leaching Risk and Improving Pear Production Through Planting and Mowing Ryegrass Mode - Haoran Fu; Qingxu Ma; Hong Chen; Lianghuan Wu; Yanmei Ye (Agronomy)
Excessive phosphorus (P) fertilization has led to high soil P accumulation in pear orchards across China, increasing the risk of P loss while limiting economic returns. Orchard grassing has been proposed as a strategy to optimize soil P content and reduce P loss; however, its limited economic benefits have hindered widespread adoption. To address this, we developed a novel planting and mowing ryegrass (MF) system, integrating P loss mitigation with improved economic returns. A two-year field experiment was conducted in the Yangtze River Basin to assess the effects of this system on soil P fractions, P loss risk, and pear production. The results showed that soil available nitrogen (N), available potassium (K), and total P content were significantly lower in the MF treatment compared to natural grassing (NG) at different growth stages. Moreover, the MF treatment increased pear yield by 14.7–16.7% and reduced titratable acidity by 23.5–47.1%, with these improvements primarily driven by changes in phosphorus-related indicators (NaOH-Pi, NaHCO3-Pi, and intermediate P) across different years. Additionally, the reduction in NaHCO3-Pi in the MF treatment contributed to a decline in P leaching risk indicators, including Olsen-P and CaCl2-P. These findings highlight the potential of the MF system as a sustainable orchard management strategy, effectively optimizing soil P dynamics, mitigating P leaching risks, and enhancing pear yield and quality under high P conditions.